SAT0293 SPECIFIC ALTERATIONS OF NAILFOLD CAPILLARIES MIGHT ANTICIPATE THE APPEARANCE OF THE EARLY CAPILLAROSCOPIC SCLERODERMA-PATTERN IN SYSTEMIC SCLEROSIS PATIENTS. (June 2019) - Pendolino, Monica; Pizzorni, Carmen; Sulli, Alberto; Paolino, Sabrina; Tomatis, Veronica; Alessandri, Elisa; Goegan, Federica; Smith, Vanessa; Cutolo, Maurizio
Abstract : Background: Non-specific abnormalities (i.e. capillary enlargements) are usually found at the nailfold videocapillaroscopy (NVC) analysis in patients affected by primary Raynaud's phenomenon (PRP). We have previously demonstrated that capillary diameter is an independent predictor for development of systemic sclerosis (SSc) associated secondary Raynaud's Phenomenon (SRP), so that progression to SRP is unlikely for subjects affected by RP when average nailfold capillary diameter is under 30 μm [1]. However, until now these findings have not been clearly classified in a defined pattern able to really predict the evolution to a scleroderma-pattern. Objectives: This pilot study aimed to identify in a cohort of SSc patients a "very early" NVC pattern at high risk of evolution in the already defined NVC scleroderma-patterns. Methods: We selected the NVCs of 273 patients affected by SSc (according to 2013 ACR criteria) who presented one of the validated NVC scleroderma patterns (81 with "Early" pattern, 84 with "Active" pattern, 92 with "Late" pattern, 16 with "scleroderma-like" pattern) (2). Among the 273 SSc patient with an established NVC scleroderma-pattern, a number of 54 subjects who had previously NVC analyses performed before the development of the scleroderma-pattern were enrolled. Time of evolution was calculated, and a detailed pilot study of capillaroscopic characteristics was random executed on 10 of those patients. The analysis included the number and the limbs diameters (arterial, venous, and apical) of capillaries with a diameter over 30 μm, together with the total number of capillaries and microhemorrhages, in 16 images per subject. Results: All the 54 patients (100%) showed enlarged capillaries with an average diameter over 30 μm in their previous NVC. At the follow up, thirty-one patients (57%) developed an "Early" scleroderma pattern in the following 3 years, 6 patients (11%) developed an "Active" pattern in 4 years, 3 patients (6%) evolved in "Late" NVC pattern in 5 years, whereas 14 patients (26%) developed a "scleroderma-like pattern" in 4 years. The average time of evolution in a scleroderma-pattern was 4 years. The detailed pilot morphological analysis conducted on 10 patients revealed an average total number of capillaries of 8.6/mm at last non-specific NVC analysis; among these 2.66 (31%) capillaries showed a diameter over 30 μm. The mean value diameter of the most dilated capillary was 35.74 μm (arterial limb 33.34 μm, apical limb 43.94 μm, venous limb 30 μm); the mean value for microhemorrhages was 0.6/mm. The mean number of capillaries reduced from 8.6±0.8 to 6.9±2.2/mm (p=0.01) during follow-up (4 years). Conclusion: Present detailed pilot study demonstrates that SSc patients showed a significant increase of nailfold capillary diameter over 30 μm before development of a validated NVC scleroderma-pattern at follow up. Even if this is an independent predictor for development of SSc as previously demonstrated, the data could help in intercepting patients with RP at higher risk of evolution in a validated SSc NVC pattern. Reference: [1] Trombetta AC, et al. J Rheumatol. 2016;43:599-606. 2. Cutolo M, et al. J Rheumatol2000;27:155-60. Disclosure of Interests: None declared